A pH-sensitive prodrug micelle self-assembled from multi-doxorubicin-tailed polyethylene glycol for cancer therapy. Issue 11 (25th January 2016) - Li, Jingguo; Zhang, Lu; Lin, Yujie; Xiao, Hong; Zuo, Mingxiang; Cheng, Du; Shuai, Xintao
Abstract : A novel tetra-doxorubicin-tailed polyethylene glycol via benzoic-imine bond linkage was synthesized and self-assembled to a pH-sensitive prodrug micelle. Abstract : A novel tetra-doxorubicin-tailed polyethylene glycol via benzoic-imine bond linkage was synthesized and self-assembled to a pH-sensitive prodrug micelle. This micelle not only effectively entered cancer cells but also quickly released doxorubicin (DOX) in tumor sites to exert anticancer activity in vitro .